PENGARUH INTENSITAS RERAN AKUNTANSI MANAJEMEN DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KUALITAS PELAYANAN SISTEM INFORMASI PERUSAHAAN - Drajat Armono (Jurnal Aplikasi Bisnis, 2017)
The objective of this research is to test the influence of intrnsity of role of accounting management and environmental uncertainty toward  service quality given by unit of information system in a company. Considering that role of accounting management is giving the information for internal party, and with the existence of high uncertainty from side external, information become a very valuable commodity for management decision making. Based on the mentioned, hence writer tried to check how big quality of service of unit information system will be affected by both the things that, and how far quality of that information system unit service give the real service comparated to on the chance of costumer. measurement of service quality is also laid open in this research, and concluded that quality of service of information system of company in mean still be unfavorable, because bigger costumer expectation compared to with the exiting fact. responders taken away from all finance managers, marketing managers, production managers, and research & development managers in some big companies having its office center in Jakarta. Quetionnare disseminated by as much 250, and only 43 competent questionare test. This research also conclude that intensity of role of accounting management and environmental uncertainty have an effect on by significant to quality of service of information system cpmpany. some implications and research limitation elaborated in this research ending